String theory and the SymTFT of 3d orthosymplectic Chern-Simons theory - Oren Bergman; Francesco Mignosa (Journal of High Energy Physics)
Abstract We revisit the 3d N $$ \mathcal{N} $$ = 5 Chern-Simons-Matter theory with orthosymplectic gauge group and its gravity dual from the perspective of generalized symmetries. We derive the corresponding 4d symmetry topological field theory from the gravity dual and relate the allowed boundary conditions to the different variants of the 3d theory. Concentrating on a specific variant that has a discrete non-abelian global symmetry, we explain how the structure of this symmetry arises from brane dynamics.